2022
DOI: 10.1136/bmjpo-2021-001273
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in children and young adults with minor injury in emergency departments in the UK and Ireland: a PERUKI service evaluation

Abstract: BackgroundManagement of acute pain should commence at the earliest opportunity, as it has many short-term and long-term consequences. A research priority of Paediatric Emergency Research in the UK and Ireland (PERUKI) was to examine paediatric pain practices.ObjectiveTo describe the outcomes for paediatric pain management of minor injuries presenting to emergency departments (EDs) across PERUKI.MethodsA retrospective service evaluation was performed over a 7-day period in late 2016/early 2017 across PERUKI sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We noticed that most of the patients attended the ED during on-call periods, which suggests that training on-call teams would be particularly useful value. The reassessment of fracture pain was not su ciently frequent in our study or in literature (from 3.5-52% of cases) (14,24,25). It might be improved by providing a tool that enable children and/or their parents to re-evaluate pain themselves, as recommended by the Task Force on Pain in Infants, Children, and Adolescents (26).…”
Section: Clinical Implicationmentioning
confidence: 64%
See 1 more Smart Citation
“…We noticed that most of the patients attended the ED during on-call periods, which suggests that training on-call teams would be particularly useful value. The reassessment of fracture pain was not su ciently frequent in our study or in literature (from 3.5-52% of cases) (14,24,25). It might be improved by providing a tool that enable children and/or their parents to re-evaluate pain themselves, as recommended by the Task Force on Pain in Infants, Children, and Adolescents (26).…”
Section: Clinical Implicationmentioning
confidence: 64%
“…In an Israelian study, a pain score was documented in fewer than 20% of patients in both PEDs and general EDs (13). A large study of practices in the UK and Ireland found that pain was documented in 57.5% of patients during their ED visit, with large variations between centers (14). In our study, almost all patients had a pain assessment; this was probably due to inclusion of a pain scale in the nurses' triage software and systematically use on admission, as described by others (15).…”
Section: Previous Studiesmentioning
confidence: 99%